2021
DOI: 10.1128/jcm.02510-20
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SARS-CoV-2 Antibodies in Oral Fluid Obtained Using a Rapid Collection Device

Abstract: Current commercially available methods for reliably detecting antibodies against SARS-CoV-2 remain expensive and inaccessible due to the need for whole blood collection by highly trained phlebotomists using personal protective equipment (PPE). We have evaluated an antibody detection approach using the OraSure Technologies’ Oral Antibody Collection Device (OACD) and their proprietary SARS-CoV-2 total antibody detection enzyme-linked immunosorbent assay (ELISA). We found that the OraSure test for total antibody … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 8 publications
0
32
0
Order By: Relevance
“…We hypothesize that mRNA vaccines may elicit a strong antibody response in the upper respiratory tract at the sites where primary infection occurs and propagates, thereby preventing SARS-CoV-2 infection and transmission. An earlier work from our group demonstrated that SARS-CoV-2 IgG antibodies targeting spike protein S1 and S2 can be reliably detected from self-collected oral fluid among participants previously infected with SARS-CoV-2 (3). In the present study, we aimed to 1) assess whether SARS-CoV-2 IgG antibodies targeting the spike protein are detectable in self-collected oral and/or nasal mucosal following COVID-19 mRNA vaccination; and 2) quantify SARS-CoV- Enrolled participants provided oral fluid specimens on days 5, 10, 15, and 20 following their first vaccination dose, and days 5, 10, 15, and 20 following their second vaccination dose.…”
Section: Introductionmentioning
confidence: 93%
“…We hypothesize that mRNA vaccines may elicit a strong antibody response in the upper respiratory tract at the sites where primary infection occurs and propagates, thereby preventing SARS-CoV-2 infection and transmission. An earlier work from our group demonstrated that SARS-CoV-2 IgG antibodies targeting spike protein S1 and S2 can be reliably detected from self-collected oral fluid among participants previously infected with SARS-CoV-2 (3). In the present study, we aimed to 1) assess whether SARS-CoV-2 IgG antibodies targeting the spike protein are detectable in self-collected oral and/or nasal mucosal following COVID-19 mRNA vaccination; and 2) quantify SARS-CoV- Enrolled participants provided oral fluid specimens on days 5, 10, 15, and 20 following their first vaccination dose, and days 5, 10, 15, and 20 following their second vaccination dose.…”
Section: Introductionmentioning
confidence: 93%
“…This would potentially lead to a decrease in demand for medical personnel and alleviate some of the strain put on the healthcare system. OraSure Technologies, Inc. has already manufactured an oral antibody collection device (OACD) that meets EUA requirements and can be self-administered under healthcare worker guidance, making it useful when available phlebotomists are limited (18). Furthermore, this advantage could reduce the risk of exposure to healthcare workers, which was a concern when collecting whole blood for testing from patients during the pandemic.…”
Section: Saliva-based Elisasmentioning
confidence: 99%
“…Figure 2 describes the DIVA strategy for the detection of anti-N antibodies, which are only elicited in individuals exposed to the whole SARS-CoV-2 virus, whereas anti-S antibodies can be detected in individuals who were previously vaccinated [ 92 ] (inactivated, mRNA, replication-incompetent vectors, or recombinant S protein vaccines) or exposed to SARS-CoV-2 infection. Importantly, DIVA can be applied for antibody detection in oral fluids, which is convenient and feasible for specimen collection and can show high sensitivity and specificity if properly optimized [ 93 ].…”
Section: Diagnosismentioning
confidence: 99%